IV admixture lecture: mastering the fundamentals of TPN and CDR / Nik Aisyah Najwa Nik Mustaffa Shapri - Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2025)
On December 3, 2024, the Department of Pharmacy Practice and Clinical Pharmacy, Faculty of Pharmacy UiTM organised an engaging lecture titled "Mastering the Fundamentals of TPN and CDR." This educational initiative, spearheaded by the teaching team of PHC 671 Applied Therapeutics in Infectious Diseases and Neoplastic Disorders aimed to equip pharmacy students; particularly those enrolled in the PHC 671 course with comprehensive knowledge and practical skills related to Total Parenteral Nutrition (TPN) and Chemotherapy Drug Reconstitution (CDR) in hospital settings.